SKEPTISISME PROFESIONAL DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGEMENT DAMPAKNYA TERHADAP KUALITAS AUDIT - Fitri Yuliani; Sukrisno Agoes; MF Djeni Indrajati (Jurnal Kontemporer Akuntansi, 2023)
This study aims to analyze the effect of professional skepticism and task complexity on audit judgment and its impact on audit quality. This research was conducted at KAP members of FAPM in Jakarta. The sample in this study was selected using a purposive sample method in order to obtain a total sample of 100 external auditors using a questionnaire. The research method used is descriptive and statistical analysis using the SmartPLS 3.0 test tool. This study shows that professional skepticism and task complexity have a positive effect on audit judgment and audit judgment has a positive effect on audit quality.